2020
DOI: 10.1038/s41598-020-66931-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid and Nonalcoholic Fatty Liver Disease in Nonobese Postmenopausal Women: A Cross-sectional Study

Abstract: This study aimed to determine the association between serum uric acid (sUA) and nonalcoholic fatty liver disease (NAFLD) in nonobese postmenopausal women. A total of 4323 female individuals over 18 years of age participated in this cross-sectional study. The subjects were divided into four groups according to menopause status and body mass index. sUA quartiles in this female population were categorized as follows: Q1 ≤ 230 mmol/L, Q2: 231–270 mmol/L, Q3: 271–310 mmol/L and Q4: ≥ 311 mmol/L. The presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…Incidentally, there have been quite a few cross-sectional and prospective observational studies with Chinese population analyzing serum uric acid and liver health. Bao et al (2020) in their study identified a relationship between serum uric acid level and NAFLD in a population of non-obese post-menopausal women [ 22 ]. Similarly, in another prospective observational study, individuals with elevated serum uric acid levels were found to have a greater potential to develop NAFLD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, there have been quite a few cross-sectional and prospective observational studies with Chinese population analyzing serum uric acid and liver health. Bao et al (2020) in their study identified a relationship between serum uric acid level and NAFLD in a population of non-obese post-menopausal women [ 22 ]. Similarly, in another prospective observational study, individuals with elevated serum uric acid levels were found to have a greater potential to develop NAFLD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an association between serum GGT and elevated SUA in normotensive Chinese individuals 22 . A recent study showed a significant positive association and dose-dependent relationship between SUA and the prevalence of NAFLD in nonobese postmenopausal population in China 23 . The elevated SUA concentration, even within the normal range also showed an association with increased ALT in Chinese adults 24 .…”
Section: Introductionmentioning
confidence: 97%
“…and performed on 541 type 2 diabetic patients, showed that UA levels were not independently associated with the risk of NAFLD in female population ( 8 ). Another study showed that the presence of UA predicted the risk of NAFLD only in nonobese postmenopausal females, rather than in obese postmenopausal females ( 30 ). However, our study found the positive association of UA and liver steatosis held true for both premenopausal and postmenopausal females, which was consistent with an early study, showing that high levels of UA were associated with NAFLD both in premenopausal and postmenopausal females ( 31 ).…”
Section: Discussionmentioning
confidence: 99%